A organização do trabalho pedagógico no Instituto Federal do Paraná – campus Palmas: implicações para o trabalho docente - Peratz, Tatiane (2019)
This research is part of the Program of Education offered by Universidade Estadual do Oeste do Paraná (UNIOESTE). It is included in the “Culture, Educational Processes and Teacher Education” research line, which aims to investigate the interrelations between culture and education, formal and non-formal educational processes in its theoreticalpractical, sociopolitical and pedagogical dimensions. The theme of this research is centered on the organization of the pedagogical work of Instituto Federal do Paraná (IFPR). Its object of analysis is the teacher’s work, specifically what refers to the implications of the organization of the pedagogical work. The purpose derives from the studies and the researches done by the research group called “Educação Superior, Formação e Trabalho Docente” (GESFORT) of which the researcher is part of. It also derives from the researcher’s teaching experiences in one of the campuses of the Institutions of Professional, Technological and Science Education and from the need to unveil the reality of this teaching organization. The objective of the research is to analyze the implications of the organization of the pedagogical work to the teacher’s work at IFPR – Campus Palmas, at the Southwest region of the State of Paraná. The methodology is based on the bibliographic research of documents and data obtained through questionnaires answered by the teachers of Campus Palmas. Federal laws, resolutions, norms and internal rules were the sources utilized. Through the analysis the vertical expansion of teaching stands out as the main implication for the teacher’s work and education, since this form of organization of the pedagogical work requires action on the distinct levels of education. With that, the pedagogical education surges as a second category, since non-licensed teachers constantly join the institution. According to Ministry of Education’s Resolution 02/2015, these teachers must take courses to obtain the required education to teach at the institution. The discussions show contradictions regarding the organization of the pedagogical and the teacher’s work. It also shows contradictions regarding the teachers’ education to work in the Professional Education. The first contradiction comes from the intentions on the education of the institution’s students: they are prepared to work, but at the same time they are prepared to be citizens. The second contradiction reveals itself during the analysis of resolutions 06/2012, 02/2015 and at PLAFOR, since deadlines to accomplish the adequate education are imposed to the teacher at the same time that there is a strict restriction over the institutions that can offer the adequate education. That means that regardless the teacher’s choice, the offering of a specific continued education course determines whether they will be able to accomplish the law.